Medication History Lab and Assessment using the Medication Mysteries Infinite Case Tool - Karen R. Sando; Randell Doty; Jennifer Elliott; Melonie L. Stanton (Association of American Medical Colleges, 2016)
Abstract Introduction Teaching medication history taking or medication reconciliation to students requires practice for students to achieve competency. Practice makes students more confident with the process, but multiple practice opportunities require multiple cases, and creating these new cases can be a tedious and time-consuming process. Methods The Medication Mysteries Infinite Case Tool was designed to produce random patient cases using game-like features to allow students to practice medication history taking and medication reconciliation without the need to use and train standardized patients. The tool was created using a random draw card-based system to determine patient personality attributes, drugs they are taking, and confusions they have about their drug-taking behavior. This tool is used in a lab dedicated for the purpose of practicing medication history taking with students being assessed via simulation with standardized patients. This tool is currently used at the University of Florida College of Pharmacy as part of a training program for first-year pharmacy students. Results Since 2011, seven classes of first- and second-year pharmacy students have participated in this lab. Each year's class contained an average of 280 students divided into lab groups of 18-24 students. In our initial offering of the lab and assessment, 200 students on three campuses completed the individual assessments following the laboratory session. Fifty-eight percent achieved excellence, and 39% achieved competence on the individual assessment. Only 3% were assessed as being deficient on their performance and were required to repeat the assessment. Overall, 86.8% agreed or strongly agreed that the MMICT was an excellent way to experience how to reconcile medication. Discussion Students enjoy the practice and become proficient with the skills they learn through this process as evidenced by increased self-efficacy and achieved competence on a standardized assessment. The tool and the research associated with the outcome were awarded with the 2012 American Association of Colleges of Pharmacy Innovations in Teaching Award.